2004
DOI: 10.1002/ijc.20524
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the nucleoside‐derived drug transporters hCNT1, hENT1 and hENT2 in gynecologic tumors

Abstract: Deoxynucleoside analogs are used in the treatment of a variety of solid tumors. Their transport across the plasma membrane may determine their cytotoxicity and thus nucleoside transporter (NT) expression patterns may be of clinical relevance. Lack of appropriate antibodies for use in paraffinembedded biopsies has been a bottleneck to undertake highthroughput analysis of NT expression in solid tumors. Here we report the characterization of 2 new antibodies raised against the low-affinity equilibrative NTs, hENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 38 publications
(45 reference statements)
6
74
0
Order By: Relevance
“…As recently reported 19 these antibodies specifically recognized single bands of 50-55 kDa in CLL protein extracts. Figure 2 shows representative Western blots of five independent CLL samples in which hENT1 (a), hENT2 (b) and atubulin were analyzed.…”
Section: Equilibrative Nucleoside Transporter Expression Pattern In Csupporting
confidence: 67%
See 2 more Smart Citations
“…As recently reported 19 these antibodies specifically recognized single bands of 50-55 kDa in CLL protein extracts. Figure 2 shows representative Western blots of five independent CLL samples in which hENT1 (a), hENT2 (b) and atubulin were analyzed.…”
Section: Equilibrative Nucleoside Transporter Expression Pattern In Csupporting
confidence: 67%
“…19 They were raised against isoform-specific domains at the intracellular loop between transmembrane domains 6 and 7. Following incubations with these primary antibodies against hENT1 and hENT2, proteins were detected with the use of secondary antibodies conjugated to horseradish peroxidase and an enhanced chemiluminiscence (ECL) detection kit (Amersham, Buckinghamshire, UK).…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…21 In fact, it has been reported that hENT1 expression, despite showing marked variability among individuals, is comparatively higher in most tumors compared to in their non-transformed tissue counterparts 38 and that hENT1 protein expression is strongly retained in gynecological tumors, particularly when compared to the highly efficient nucleoside-derived drug transporter protein hCNT1. 39 A general consensus in the field is that hENT1 is a ubiquitous, highly expressed transporter protein that can account for most of the nucleoside supply required for salvage processes, particularly during tissue growth. Uncontrolled proliferation processes do not appear to be implicated in the development of CLL and, in accordance with what has been discussed above, hENT1 expression contributes only slightly to fludarabineinduced cytotoxicity in CLL cells, 12,14 even though fludarabine is a hENT1 substrate.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In some gynaecological tumors, the expression of CNT1 was found to be reduced, and this reduction of CNT1 protein was correlated with poor prognosis. 28 The SNP G565A results in reduced affinity for gemcitabine. 29 Response to chemotherapy will be influenced both by a patient's genetic background, i.e.…”
mentioning
confidence: 99%